Cara mudah & cepat sukses agribisnis semut rangrang / Bondan Zakaria, Hasan Nugroho, Wiji Budi Santoso ; editor Seno. - BONDAN ZAKARIA, 1987-; Hasan Nugroho; Wiji Budi Santoso; Seno (Lily Publisher, 2013)
vi, 62 hlm. : ilus. ; 21 cm